A study on the generalised space of urban–rural integration in Beijing suburbs during the present day. (November 2015) - Song, Zhijun; Yu, Linjun
Urban–rural integration is a complex process in the giant urban–rural system of the Beijing suburbs with various evolutions in modern suburban functions. Therefore, the functions and processes of the whole Beijing suburb system cannot be treated in isolation. Based on the theory of generalised space proposed by Chen (2008), the urban–rural integration process in the Beijing suburbs was analysed in real space (R-space), phase space (P-space) and order space (O-space). The results show that the macro urban–rural gap is the dominant factor in the O-space. A multifunctional policy at the meso-level will promote the scientific evolution of the P-space. These factors in turn influence the evolution of the urban–rural integration in Beijing suburbs at various levels in the R-space. Finally, new features of spatial organisation, for example, fractals, are generalised from the interactions of those three spaces. Therefore, the perspective of the R-P-O space fusion can provide theoretical guidance to investigators for the urban–rural integration of Beijing suburbs.